The Concept of Moral Conscience in Ancient Greek Philosophy - Mantzanas, Michail (Conatus - Journal of Philosophy, 2020)
The concept of consciousness in ancient Greek philosophy, concerns the internal autonomy and philosophical freedom from the condemnation of ignorance of both the foreign and the domestic world. The ancient Greek philosophers pointed out the value of the dialectic with the inner self to the problem of moral conscience and handed us a legacy of values and the primacy of reason. The concept of moral consciousness in ancient Greek philosophy. The article examines the concept of moral consciousness in ancient Greek philosophy. The purpose of the article is to investigate the moral question related to whether moral concepts have a subjective or an objective basis. In addition, the article demonstrates the unaffected by time significance of the concept of moral consciousness, as well as its connection with the reality of moral concepts, moral propositions, moral judgments, moral man, moral law, moral idealism, moral naturalism and moral relativism. Moral consciousness is the mirror of our self-knowledge.